2020
DOI: 10.1002/asia.202000138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkyl Groups in Pyrene Chromophore on the Mechanical Response of Pyrene‐Octafluoronaphthalene Co‐Crystals

Abstract: Changes in the photophysical properties of pyrene (Py)-octafluoronaphthalene (OFN) co-crystals (Py·OFN) upon mechanical stimuli are described herein. The Py·OFN cocrystal showed a mechano-induced bathochromic shift in emission, and a similar tendency was observed for the 1,3,6,8-tetramethylpyrene-OFN co-crystal. These shifts are due to disruption of the microscopic molecular orientation in the co-crystal, which allows for excimer formation. In sharp contrast to the parent Py·OFN and methyl-substituted Py-OFN c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…67 In only two cases has grinding-induced red-shifted emission been attributed to the formation of excimer [68][69][70][71] and the change in molecular conformation. 3 First, Iwasaki and co-workers 72 reported that the fluorescence of Pyoctafluoronaphthalene cocrystals showed a red-shift from single-molecular Py emission to Py excimer emission by grinding. Nevertheless, this situation can be easily excluded in terms of the lifetime of amorphous powder because the lifetime of excimer fluorescence often lasts as long as tens or hundreds of nanoseconds (<300 ns) in an organic aromatic system.…”
Section: Resultsmentioning
confidence: 99%
“…67 In only two cases has grinding-induced red-shifted emission been attributed to the formation of excimer [68][69][70][71] and the change in molecular conformation. 3 First, Iwasaki and co-workers 72 reported that the fluorescence of Pyoctafluoronaphthalene cocrystals showed a red-shift from single-molecular Py emission to Py excimer emission by grinding. Nevertheless, this situation can be easily excluded in terms of the lifetime of amorphous powder because the lifetime of excimer fluorescence often lasts as long as tens or hundreds of nanoseconds (<300 ns) in an organic aromatic system.…”
Section: Resultsmentioning
confidence: 99%
“…The distinct AP interaction could further be evidenced by other spectral measurements. As shown in Figure 3 a, compared with the absorption spectrum of individual R ‐Py colloidal suspension, the absorption spectrum of AP complex of R ‐Py/OFN shows no obvious change, suggesting that the addition of OFN does not affect the ground state properties of R ‐Py [13a, 15a, 18] . However, the fluorescence spectrum of R ‐Py/OFN shows significant blue‐shift from 508 nm ( R ‐Py colloidal suspension) to 480 nm, indicating the existence of strong AP interaction (Figure 3 b).…”
Section: Figurementioning
confidence: 95%